1991
DOI: 10.1007/bf02041249
|View full text |Cite
|
Sign up to set email alerts
|

Discharge pattern analysis suggests existence of a low-threshold calcium channel in cold receptors

Abstract: The regular periodic activity patterns of mammalian cold receptors have been quantitatively studied. Analysis of the timing of either single impulses or impulse groups demonstrated that the periodic receptor process is maintained independently of impulse generation and continues to operate under conditions when afferent impulses are not initiated. These results imply that the underlying conductances must be operational at threshold potentials related to impulse generation. In addition to temperature, the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Figure 2 illustrates the impulse activity of a peripheral cold receptor of the cat's tongue. These data were recorded under reduced external calcium concentrations which enhance the periodicity of the impulse patterns [Schäfer et al, 1986[Schäfer et al, , 1991 and therefore, demonstrate, particularly clearly, the main characteristics of oscillating spike-generation. Cold receptors respond to cooling steps (lowest trace, T ) with a dynamic frequency overshoot, i.e.…”
Section: Temperature Dependent Modulation Of Periodic Impulse Patternsmentioning
confidence: 84%
See 1 more Smart Citation
“…Figure 2 illustrates the impulse activity of a peripheral cold receptor of the cat's tongue. These data were recorded under reduced external calcium concentrations which enhance the periodicity of the impulse patterns [Schäfer et al, 1986[Schäfer et al, , 1991 and therefore, demonstrate, particularly clearly, the main characteristics of oscillating spike-generation. Cold receptors respond to cooling steps (lowest trace, T ) with a dynamic frequency overshoot, i.e.…”
Section: Temperature Dependent Modulation Of Periodic Impulse Patternsmentioning
confidence: 84%
“…More recently, it has become established that such patterns essentially contribute to sensory encoding mechanisms in thermo-and electroreceptors [Braun et al, 1980[Braun et al, , 1984[Braun et al, , 1994Schäfer et al, 1991;Schäfer et al, 1995] and also seem to be involved in mechanoreception [Sokabe et al, 1993]. Only during recent years, similar impulse patterns have been recorded from diverse cortical and subcortical neurons of the mammalian brain where they could be related to so-called subthreshold oscillations, i.e.…”
Section: Periodic Impulse Patterns With the Contribution Of Noisementioning
confidence: 99%
“…At static temperatures above ϳ30°C the activity consists mainly in regularly fired single spikes, while at lower temperatures the bursting activity prevails (Iggo 1969). The transitions between these different spiking patterns are continuous, and their temporal structure suggests that all the different patterns can be attributed to slow oscillations of the membrane potential that are systematically altered by temperature (Braun et al 1980(Braun et al , 1998Schafer et al 1991). Acute cooling leads to a transient rise in mean frequency caused by an immediate increase in the frequency of bursts followed by an increase in burst duration and number of impulses per burst while the frequency of bursts decreases (Braun et al 1980).…”
mentioning
confidence: 99%
“…In contrast, the ionic mechanisms underlying the rhythmic firing activity exhibited by peripheral cold receptors are still unknown. Experimental evidence suggests the involvement of slow, TTX-resistant persistent sodium currents (Brock et al 1998;Herzog et al 2001) and low-threshold calcium channels (Schafer et al 1982(Schafer et al , 1991 in the underlying oscillations that generate rhythmic firing. Mathematical simulations (Braun et al 1998;Longtin and Hinzer 1996) have shown that the usual effect of temperature on ion channel gating kinetics [Q 10 ϳ3; Hille 2001] is enough to reproduce the temperature-induced change of spiking pattern in a slow wave bursting model (Plant 1981).…”
mentioning
confidence: 99%
“…For example, mammalian cold receptor afferents produce bursts of impulses when chilled [1][2][3][4][5][6] ; the oscillations arise from slow ion channels of afferent terminals. 7 Odorants evoke synchronized local field oscillations in populations of olfactory receptor neurons in the olfactory epithlium of catfish, 8 and waves of neural activity in the olfactory bulb of turtles, 9 and in olfactory networks of certain molluscs.…”
Section: Introductionmentioning
confidence: 99%